Assessing the pathogenicity of BRCA1/2 variants of unknown significance: Relevance and challenges for breast cancer precision medicine - De Paolis, Elisa; Paris, Ida; Tilocca, Bruno; Roncada, Paola; Foca, Laura; Tiberi, Giordana; D’Angelo, Tatiana; Pavese, Francesco; Muratore, Margherita; Carbognin, Luisa; Garganese, Giorgia; Masetti, Riccardo; et al. (Frontiers in Oncology, 2023)
Breast cancer (BC) is the leading cause of cancer-related death in women worldwide. Pathogenic variants in BRCA1 and BRCA2 genes account for approximately 50% of all hereditary BC, with 60-80% of patients characterized by Triple Negative Early-Stage Breast Cancer (TNBC) phenotype. The identification of a pathogenic BRCA1/2 variant has important and expanding roles in risk-reducing surgeries, treatment planning, and familial surveillance strategies. Otherwise, finding unclassified Variants of Unknown Significance (VUSs) limits the clinical utility of the molecular test, leading to an “imprecise medicine”. In line with the ongoing efforts to uncertain variants classification, we speculated about the relevance of an in-depth assessment of pathogenicity of BRCA1/2 VUS for a personalized management of patients with BC, reporting an explanatory example from our large cohort of patients. We described the tailored molecular characterization strategy adopted for a BRCA1 VUS carrier woman with a diagnosis of TNBC and a strong family history of BRCA-related cancers to underlined that the efficient integration of clinical data with the widest number of supporting molecular evidences should be adopted for the proper management of such patients, with the final aim of effectively guide the best prognostic and therapeutic paths.